A modified method for upper eyelid reconstruction with innervated orbicularis oculi myocutaneous flaps and lower lip mucosal grafts. (June 2021) - Yoshitatsu, Sumiko; Shiraishi, Makiko
Abstract: Background: Numerous reports have described methods for repairing full-thickness upper eyelid defects using lower eyelid tissue. To avoid sacrificing the lower eyelid and thereby prevent lower eyelid sagging or dysfunction, we used innervated orbicularis oculi myocutaneous flaps harvested from the upper eyelid for upper eyelid reconstruction. Methods: We modified a method reported by Moschella and Cordova for repairing full-thickness upper eyelid defects using innervated bipedicled orbicularis oculi myocutaneous flaps mobilized from the upper eyelid and labial mucosal grafts. First, we avoided the use of a Fricke flap, which is used in the original method to repair the myocutaneous flap donor site, since it can cause asymmetry of the eyebrows on both sides. Second, reconstruction of the double-fold eyelid was performed with buried sutures in the myocutaneous flap in secondary surgery, since the double eyelid fold of the original method is not necessary or is too wide for Asian people. Functional and cosmetic outcomes were assessed by six evaluators using postoperative photographs. Results: Six patients with malignant upper eyelid tumours underwent repair of upper eyelid defects by our modified method. Donor sites of the myocutaneous flaps were repaired with a medial forehead flap in one patient with Merkel cell carcinoma, a lateral orbital flap in one patient with sebaceous carcinoma, and a two-stage skin graft in two patients with sebaceous carcinoma and basal cell carcinoma, respectively. The two remaining patients (one with sebaceous carcinoma and the other with basal cell carcinoma) required no donor site repair. Functional and cosmetic outcomes were good or excellent in most cases. Conclusion: Our modified method for repairing full-thickness upper eyelid defects using innervated orbicularis oculi myocutaneous flaps resulted in optimal eyelid function and support, with morphologically satisfactory results including bilateral symmetry. This method provides a useful alternative to conventional methods of upper eyelid reconstruction.